Principy rezistence makrofagu vuci intracelularnim parazitum - Novosad, Jakub; Holická, Monika; Novosadová, Martina; Krčmová, Irena; Malá, Eva; Krejsek, Jan (Klinicka mikrobiologie a infekcni lekarstvi, 2010)
Intracellular parasitism is a phenomenon present in nature for more than one billion years. Its keystone is the intriguing ability of viruses and some bacteria to survive and multiply inside eukaryotic host cells and to parasitize on their metabolic machinery. According to the classical definition, germs are classified as intracellular parasites only if they are able to survive inside macrophages. However, the ability of germs to survive inside eukaryotic cells is much more common than it was expected earlier. Reaction of macrophages to invading microbes is the key point in the complex immunological resistance of the host. The outcome of the host is substantially linked to macrophage reactivity. For example, if an evading microbe with a replication time of 20 minutes survived inside a host for 24 hours without reaction of innate immunity, there would be more than 2 x 1021 microbes at the end of this period. It would be fatal for the host, indeed. The key activities of macrophages in the sense of protection against intracellular parasites are reviewed. Some mechanisms of microbial defence and some new approaches to clinical diagnosis of the functional status of cells of innate immunity are also discussed.
Keywords: interferon gama; Macrophages; Host-Pathogen Interactions; MAP Kinase Signaling System; MAP kinasový signální systém; Inflammasomes; Immunity, Innate; Signal Transduction; Humans; Interferon-gamma; interakce hostitele a patogenu; lipopolysacharidy; Macrophage Activation; lidé; inflamasomy; aktivace makrofágů; NF-kappa B; Lipopolysaccharides; přirozená imunita; signální transdukce; makrofágy